Responsible entrepreneurship education emerging research and opportunities - Marzi, Giacomo, 1989-; Caputo, Andrea, 1986- (Business Science Reference, 2019)
"This book analyzes the research contributions in the field of entrepreneurial training and investigates the concept of knowledge and creativity in this context. It also examines the psychological side of entrepreneurship behavior to understand what drives this behavior in individuals so they achieve a goal of greater personal and economic well-being"--